Teaching human anatomy to the visually impaired: A systematic review. Issue 5 (25th April 2022) - de Lima, Paola; Souza e Silva, Renata; Guedert, Denis Guilherme; Costa, Ana Carolina Figueiredo; Gondim, Delane Viana; Vale, Mariana Lima
Abstract: Information related to human anatomy is present throughout the educational process, especially in undergraduate courses in the biomedical area. These courses have complex theoretical and practical contents, and this becomes more evident when they are developed for the visually impaired. The objective of this work was to perform a systematic review on the teaching of human anatomy for the visually impaired. After the protocol was registered on the PROSPERO platform (CRD42022306002), 10 electronic databases were manually searched with the descriptors "teaching human anatomy" and "visually impaired." Intervention studies were selected without date or language restrictions. In the end, only eight studies were found. Tactile materials produced manually, and Braille and cadaveric pieces, are assessed as good tools for teaching human anatomy to the visually impaired. There is a pressing need for adaptations of teaching methods to make the teaching more accessible and inclusive.